(untitled) (Bangladesh Heart Journal, 2021)
Pharmacological therapy is mostly employed in the management of supraventricular tachyarrhythmias in different part of the world including Bangladesh. However, Radiofrequency catheter ablation has been found to be highly effective and safe in the treatment of such tachyarrhythmias. Objective: The current study is aimed at sharing our experiences of 842 patients who presented with Supraventricular tachycardias and were diagnosed by EPS and treated with Radiofrequency catheter ablation. Methods: This descriptive study has been carried out in the cardiac electro physiology Department of NICVD, Dhaka, Bangladesh from 2nd January 2015 to 31st December, 2020. Electrophysiology study(EPS) was carried out to identity and diagnose the mechanism of different SVTs in 842 consecutive patients. RF catheter ablation was used to interrupt the tachycardia circuit. Results: Out of a total 842 patients who underwent Electrophysiology study, 435 were found to have atrioventricular nodal re-entry tachycardia (AVNRT) as underlying mechanism and 391 were having accessory pathway responsible for the reentry mechanism; of these accessory mediated tachycardia, 250 patients were manifested accessory pathway (WPWS); 141 were concealed accessory pathway (out of them 365 were presented with orthodromic and 26 as antidromic reciprocating tachycardia); moreover among the accessory pathway 231 patients were found having left sided accessory pathway whereas 155 having right sided pathway; 12 patients were having focal atrial tachycardia and 4 were found atrial flutter as the underlying cause for SVT. Radiofrequency catheter ablation was used with an overall success rate of 95%, recurrence rate of 2% without any significant complication. Complication: One patient developed pulmonary thrombo-embolism, 6 patients developed DVT of right lower limb, 4 patients developed complete heart block. Conclusion: RF catheter ablation is safe and highly effective mode of treatment of different types of supraventricular tachyarrhythmias which is emerging and becoming popular in our country. Bangladesh Heart Journal 2021; 36(2): 68-73